Molecular strategies to inhibit ABC Transporters in Prevotella intermedia: Overcoming Periodontal Pathogenesis via Molecular Modelling and docking studies - Bharadwaz, Snigdha; Jishnu, Jishnu (Journal of Neonatal Surgery, 2025)
Periodontal diseases, including gingivitis and periodontitis, are chronic inflammatory conditions driven by complex microbial interactions within the oral cavity. Prevotella intermedia, a Gram-negative anaerobic bacterium, is a key contributor to periodontal pathogenesis due to its virulence factors and ability to thrive in subgingival environments. Among its survival mechanisms, ATP-binding cassette (ABC) transporters play a crucial role in nutrient acquisition, toxin efflux, and antimicrobial resistance. This study aims to explore molecular strategies for inhibiting ABC transporters in P. intermedia using computational approaches such as molecular modelling and docking analysis. The three-dimensional structure of the ABC transporter protein was retrieved from the RCSB Protein Data Bank, while potential inhibitory ligands were selected from the Antimicrobial Peptide Database. Molecular docking was performed using ClusPro to evaluate protein–ligand interactions. The results demonstrated that selected peptides exhibited favorable binding affinities and stable interactions with key functional domains of the transporter. These findings suggest that targeting ABC transporters could impair bacterial survival and reduce pathogenicity. However, further experimental validation is required to confirm these computational predictions. This study highlights the potential of computational drug design in identifying novel therapeutic targets for periodontal diseases and provides a foundation for future translational research